The shuttle walking test: a reproducible method for evaluating the impact of shortness of breath on functional capacity in patients with advanced cancer. Issue 2 (1st February 2001) - Booth, S; Adams, L
Abstract : BACKGROUND: Breathlessness leading to exercise limitation is common in patients with advanced cancer and is ineffectively treated. There are few research data to guide clinicians on best practice. The shuttle walking test has been validated for some conditions such as chronic obstructive pulmonary disease but not for advanced cancer. One of the well documented difficulties of doing clinical research in palliative care is the acceptability of assessment tests. This study examined the reproducibility of the shuttle walking test in patients with advanced cancer to help facilitate the systematic evaluation of interventions designed to improve breathlessness. METHODS: Patients performed three shuttle walks on separate days with continuous monitoring of arterial oxygen saturation and heart rate; simple pulmonary function (FEV1 ) was also recorded. Data on quality of life, anxiety, and depression were collected throughout the study period using appropriate questionnaires. Breathlessness was measured before and after exercise using a visual analogue scale. RESULTS: Data from 22 patients were compared between visits 2 and 3. There were no significant differences between the FEV1 (1.89 v 1.90, p=0.73), distance walked on each test (245 m v 256 m, p=0.14), end-exercise levels of heart rate (107/min v 108/min, p=0.11), oxygen saturation (93.4% v 93.2%, p=0.38), or breathlessness scores (p=0.62) on the two occasions. Indices of quality of life, anxiety, and depression were also not different between the two tests. The investigation was very acceptable to patients, families, and staff. CONCLUSIONS: The shuttle walking test is a reproducible test of functional capacity in ambulant patients with advanced cancer, WHO performance status 1 or 2. The data indicate that a practice session is needed. It is easy to carry out and acceptable for patients with advanced cancer.